Prospective comparison of primary wound closure with tissue- adhesive versus suture materials - Marbin, Rasim Yousif; Fattah, Jalal Hamasalih (Zanco Journal of Medical Sciences (ZJMS), 2015)
Background and Objectives: Nowadays the final outcome of wound closure using tissue adhesives and suture material is making a real competition for better results. Cosmetic outcome is regarded as the first demand for the patients. The aim of this study was to make a comparison between the two closure methods in terms of cosmetic outcome, complication and patients’ satisfaction. Method: A prospective comparative study was conducted at Rizgary Teaching Hospital and West Erbil Emergency Hospital in Erbil city from March 2012 to March 2013. A total of 105 patients were included in the study. The method of closure was selected alternatively between tissue adhesive (octylcyanoacrylate) and suture material. Analysis for cosmetic outcome, complications and patients’ satisfaction were done using the statistical package for the social sciences (version 19). Results: The complications were 25% (13 patients) in the tissue adhesive group and 18% (9 patients) in the sutured group. Of the 44 patients in the tissue adhesive group, 86.4% (38 patients) were satisfied; while of the 61 patients in the sutured group, 88% (54 patients) were satisfied with the end result. Excellent cosmetic outcome achieved in 77.3% in the tissue adhesive group and 80.3% in the sutured group. Conclusion: Tissue adhesive (octylcyanoacrylate) is effective and reliable in primary skin closure, yielding similar cosmetic results to standard suturing method. Tissue adhesive is faster and offers several practical advantages over suture repair.